Digital Influencers and Their Effect on Brand Perception and Loyalty - Rezki, Rezki (Journal of Social Commerce, 2023)
This quantitative research examines the impact of digital influencers on brand image and brand attitude, with particular focus on influencer credibility. Based on a survey of 500 respondents, the study uses correlation analysis, regression analysis, analysis of variance and covariance analysis to determine the effects of influencer credibility, perceived brand image, and brand loyalty. This research shows that perception of brands has significant positive relationship with influencer credibility and credibility alone can be used to predict brand perception. Further, the proposed influencer credibility-have a direct effect on brand loyalty,which is over and above the effect through brand perception, which in turn has a proposed positive and significant mediating effect between credibility and loyalty. The study also establishes that, there is a disparity in the impact of different influence towards brand loyalty. The study minimizes the threat of confounding variables such as the frequency of social media usage thereby providing a clear idea of the factors that affect brand results. These research endeavors add further knowledge to the already existent literature on influencer marketing based on the details that denote the way through which influencer credibility influences the consumer behaviors in addition to offering some real-life strategies for marketers.